Accounting best practices - Bragg, Steven M. ([Wiley best practices], 2010)
"Accounting Best Practices, Sixth Edition offers the latest and most important information on advanced techniques and strategies to help you increase productivity, reduce costs, and efficiently monitor a company?s existing systems." "This new Sixth Edition has been fully updated to include ninety new best practices included in the chapters on Treasury Management, Billing, Accounts Payable, Payroll, and Inventory. In addition, two new chapters have been added on credit and collections."--BOOK JACKET.